2011
DOI: 10.1126/science.1207785
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation History of Itokawa Regolith Material Deduced from Noble Gases in the Hayabusa Samples

Abstract: Noble gas isotopes were measured in three rocky grains from asteroid Itokawa to elucidate a history of irradiation from cosmic rays and solar wind on its surface. Large amounts of solar helium (He), neon (Ne), and argon (Ar) trapped in various depths in the grains were observed, which can be explained by multiple implantations of solar wind particles into the grains, combined with preferential He loss caused by frictional wear of space-weathered rims on the grains. Short residence time of less than 8 million y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 25 publications
7
93
2
2
Order By: Relevance
“…7 shows that the impactor flux on Itokawa particles is at least one order of magnitude higher than the interplanetary dust flux ( T = 10 4 yr) and comparable to the case of the Moon ( T = 10 2 to 10 3 yr). Considering that T = 10 2 to 10 3 yr is most likely the direct-exposure age according to the noble-gas analysis ( Nagao et al, 2011 ), we conclude that secondary ejecta impacts are probably the dominant cratering process in the submicrometersize range on Itokawa regolith particles, as well as on the lunar surface.…”
Section: Origin Of Submicrometer Cratersmentioning
confidence: 78%
See 2 more Smart Citations
“…7 shows that the impactor flux on Itokawa particles is at least one order of magnitude higher than the interplanetary dust flux ( T = 10 4 yr) and comparable to the case of the Moon ( T = 10 2 to 10 3 yr). Considering that T = 10 2 to 10 3 yr is most likely the direct-exposure age according to the noble-gas analysis ( Nagao et al, 2011 ), we conclude that secondary ejecta impacts are probably the dominant cratering process in the submicrometersize range on Itokawa regolith particles, as well as on the lunar surface.…”
Section: Origin Of Submicrometer Cratersmentioning
confidence: 78%
“…In addition, microscopic meteoroid impacts contribute to changes in the optical properties, chemical composition, and structures of regolith surface material ( Noguchi et al, 2011;Harries and Langenhorst, 2014;Keller and Berger, 2014;Noguchi et al, 2014;Thompson et al, 2014;Bonal et al, 2015;Matsumoto et al, 2015;Harries et al, 2016;Matsumoto et al, 2016 ). In addition, regolith activity on Itokawaprobably driven by impact processes-has been identified based on grain motion ( Nagao et al, 2011;Matsumoto et al, 2016 ), fracturing ( Tsuchiyama et al, 2011;Langenhorst et al, 2014 ;Matsumoto et al, 2016 ), and abrasion ( Tsuchiyama et al, 2011 ). These previous studies have shown that Itokawa particles contain a record of the collective processes of regolith evolution on this small asteroid.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Asteroidal materials occurring as meteorites have been studied in detail. In particular, those recovered from the asteroid Itokawa by the Hayabusa spacecraft have been subjected to comprehensive studies (e.g., Nakamura et al 2011;Noguchi et al 2011Noguchi et al , 2014aNoguchi et al , 2014bNagao et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011;Nakamura et al 2012;Harries and Langenhorst 2014;Keller and Berger 2014;Langenhorst et al 2014;Mikouchi et al 2014;Thompson et al 2014;Takeda et al 2015). In contrast, it is difficult to obtain samples identified to be cometary in origin, with the exception of direct sampling by the Stardust mission that returned the dust samples from the short-period comet 81P/Wild 2 (Zolensky et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the Japanese Space Agency's (JAXA) Hayabusa mission was the first to focus on an asteroid with an aim to return a sample (Fujiwara et al, 2004). With only a basic scientific payload onboard Hayabusa, data gathered on the S-type asteroid Itokawa have nevertheless yielded incredible results (Nagao et al 2011, Tsuchiyama et al 2011) Ideas for visiting a Vtype NEO in a sample return mission are presented in the work of Duffard et al (2011).…”
Section: Mineralogy Of Basaltic Materials On the Minor Bodies Of Our Smentioning
confidence: 99%